KEMAMPUAN SOSIALISASI DAN GERAK MANIPULATIF BERBASIS KELOMPOK PADA ANAK USIA 4-5 TAHU - Mohamad Syarif Sumantri; Tjia Endrawati (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
The purpose of this study is to answer the problem of how to improve the social skills of children aged 4-5 years through group -based manipulative motion activity. The research was carried out in the children group of 4-5 years old at The Kindergarten of IPEKA Sunter, North Jakarta as from March through May 2011. The research method used an action research approach through cycles: initial assessment planning, action, observation and reflection, the research carried out in 2 cycles, data collected by the instrument type observation, interviews and documents,with mixmethod data analysis, and data validity by triangulation methods and sources. The results of data analysis show an overall group -based manipulative movement has increased the social skills of children aged 4-5 years was 76.77 % , makes no difference that drives the improvement of learning outcomes is through manipulative motion activity -based group has given children the opportunity to interact intensively, fun atmosphere, providing the freedom of choice of activity , active child, role sharing, collaboration, and empathy. The implication of this study is if the activity group -based manipulative movement properly made and programmed it will have a positive impact on the development potential of the socialization of children.